Chemical synergies : from the lab to in silico modelling - Alemán, Carlos; Ambrogi, Veronica; Bandeira, Nuno A. G.; Bertran, Oscar; Cerruti, Pierfrancesco; Costa, Paulo; Fianchini, Mauro; Giamberini, Marta; Gulaczyk, Iwona; Jastrzab, Renata; Kaczmarek, Malgorzata Teresa; López, Xavier; et al. (De Gruyter, 2018)
This book gives an overview of recent integrated and inter-disciplinary approaches between chemical experiment and theory in a variety of fields, from polymer science to materials chemistry and ranging from the design of tailored properties to catalysis and reactivity, building on the well-established success of Density Functional Theory as the foremost quantum chemical method to provide qualitative and quantitative interpretation of results from the chemical laboratory. The combination of several characterization techniques with an understanding at the molecular level of chemical and physical phenomena are the main focal point of the subject matter.